Gestión de cuentas y documentos por pagar en la Empresa Colbapi. S.A de la ciudad de Babahoyo, períodos 2021 y 2022. - Murillo Pinto, Anthony Andrés (2024)
This case study is based on the management of accounts and documents payable in the company COLBAPI. S.A of the city of Babahoyo, periods 2021 and 2022, the same one that is related to the line of research Financial, administrative, tax, audit and control management, and is contextualized in the sub-line of Audit and control, because the company is dedicated to the marketing of hardware products; The work was carried out with the objective of determining the effectiveness of the process and use of accounts and documents payable in the periods 2021 and 2022. For the development of the case study it was necessary to use two paradigmatic modalities such as qualitative and quantitative accompanied by the types field, bibliographic and descriptive research. In addition, synthetic and inductive methods were applied, as well as survey, interview and documentary analysis techniques with their respective instruments: interview guide, survey questionnaire and financial ratios. This allowed obtaining the results that were expressed in their respective section. Therefore, the study concludes that the current accounts and documents payable category experienced a positive variation because the company purchased more products through financing, the accounts payable turnover increased in 2022, the company took 193 days to cancel their obligations, and the main advantages and disadvantages of the application of financial leverage is the increase in benefits and risk of failing to comply with obligations.